CCN1 promotes APRIL/BAFF signaling in esophageal squamous cell carcinoma but attenuates it in esophageal adenocarcinoma - Lingling Xing; Zhenyu Jiang; Ruize Xu; Tong Dang; Jinbao Wu; Jianyuan Chai; Xianmei Meng (Scientific Reports)
Abstract CCN1 is a matricellular protein highly expressed in esophageal squamous cell carcinoma (ESCC) but hardly detectable in esophageal adenocarcinoma (EAC). Expression of CCN1 in EAC cells leads to TRAIL-mediated apoptosis. Unlike TRAIL, which primarily triggers cell death, APRIL and BAFF promote cell growth via NFκB signaling. They become active ligands by Furin cleavage. This study found that CCN1 upregulated APRIL and BAFF expression in both ESCC and EAC cells but attenuated their signaling in the latter. CCN1 kept Furin stable in ESCC allowing APRIL/BAFF to signal through their common receptor BCMA properly. In EAC cells, however, expression of CCN1 lowered Furin activity and thus limited APRIL/BAFF cleavage. As a result, ESCC cells benefited from CCN1 while EAC cell viability was attenuated by it.